Building Islamic Culture to Support Students’ Religious Character Development: A Best Practices from Malaysia - Cahyanto, Bagus; Atiqoh Bela Dina, Lia Nur; Yauma Ulmy, Adella; Binti Kampun, Hdariyani; Daroini, Hasanatud; Farahdilla, Ariska (Universitas Islam Lamongan, 2025)
This study aims to explore how Islamic school culture can support the formation of students' religious character in elementary schools, namely at Madrasah Utsmaniah (ABIM) Malaysia. This study uses a qualitative phenomenological approach to explore the phenomena that occur in depth with a focus on the formation of Islamic culture that supports the formation of students' religious character in schools. The results of the study indicate that Madrasah Utsmaniah (ABIM) has implemented several strategies involving routine religious activities such as congregational prayer, teaching interpretation, and joint prayer, as well as the integration of Islamic values in various subjects. In addition, strengthening institutional governance based on Islamic principles also plays a role in creating a conducive environment for the formation of students' religious character. The findings of this study can be used as additional references related to character education and provide practical direction for Islamic schools in efforts to strengthen students' religious character through an Islamic school culture approach. Recommendations for further research are to expand the scope by involving several schools with different typologies to obtain a more varied picture of the influence of Islamic school culture on the formation of religious character.